Exposure to Umbelliferone Reduces Ralstonia solanacearum Biofilm Formation, Transcription of Type III Secretion System Regulators and Effectors and Virulence on Tobacco - Yang, Liang; Li, Shili; Qin, Xiyun; Jiang, Gaofei; Chen, Juanni; Li, Bide; Yao, Xiaoyuan; Liang, Peibo; Zhang, Yong; Ding, Wei (Frontiers in Microbiology, 2017)
Abstract: Ralstonia solanacearum, which causes bacterial wilt, one of the most devastating phytopathogens, causing severe economic loss due to its worldwide distribution and broad host range. Certain plant-derived compounds (PDCs) can impair bacterial virulence by suppressing pathogenic factors of R. solanacearum. However, the inhibitory mechanisms of PDCs in bacterial virulence remain largely unknown. In this study, we screened a library of coumarins and derivatives, natural plant-derived compounds with fused benzene and α-pyrone rings, for their effects on expression of the type III secretion system (T3SS) of R. solanacearum. Here, we show that umbelliferone (UM), a 7-hydroxycoumarin, suppressed T3SS regulator gene expression through HrpG-HrpB and PrhG-HrpB pathways. UM decreased gene expression of six type III effectors (RipX, RipD, RipP1, RipR, RipTAL and RipW) of ten representative effector genes but did not alter T2SS expression. In addition, biofilm formation of R. solanacearum was significantly reduced by UM, though swimming activity was not affected. We then observed that UM suppressed the wilting disease process by reducing colonization and proliferation in tobacco roots and stems. In summary, the findings reveal that UM may serve as a plant-derived inhibitor to manipulate R. solanacearum T3SS and biofilm formation, providing proof of concept that these key virulence factors are potential targets for the integrated control of bacterial wilt.